The IoT: Uses and Applications - Alghalith, Nabil (Journal of Strategic Innovation and Sustainability, 2020)
The Internet of Things (IoT) is a pervasive web in which each object or machine has a unique identity and is be able to use the Internet to link with other machine or send data; also known as the industrial Internet(Laudon, 2019). IoT makes it easier for people to communicate, collaborate with each other, and access educational resources, creating a multitude of opportunities for consumers, educators, and business owners to transform their lives. The following report defines the Internet of Things, provides several examples of how IoT technology is currently used, and explains the potential applications of IoT in an educational setting. The Internet-enabled devices used with the Internet of Things are useful in preschools, elementary and secondary schools, and colleges and universities, as they increase efficiency, facilitate better interactions between students and educators, and give educators more time to deliver instructional content. The report concludes with an overview of the barriers that make it difficult to implement IoT technology.